2021
DOI: 10.3390/ijms22189900
|View full text |Cite
|
Sign up to set email alerts
|

The Intra- and Extra-Telomeric Role of TRF2 in the DNA Damage Response

Abstract: Telomere repeat binding factor 2 (TRF2) has a well-known function at the telomeres, which acts to protect the telomere end from being recognized as a DNA break or from unwanted recombination. This protection mechanism prevents DNA instability from mutation and subsequent severe diseases caused by the changes in DNA, such as cancer. Since TRF2 actively inhibits the DNA damage response factors from recognizing the telomere end as a DNA break, many more studies have also shown its interactions outside of the telo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 172 publications
(177 reference statements)
0
11
0
Order By: Relevance
“…Unspecific binding of TRF2 to non-telomeric regions may not be surprising given that TRF2 has been shown to bind to other sequences (e.g. with G-quadruplex motifs) to functionally regulate the expression of several genes through epigenetic modification on the promoter (Imran et al, 2021 ; Mukherjee et al, 2019 ). TRF2 also plays a role in neuronal gene silencing, stem cell fate and cancer cell survival through its interaction with repressor element 1-silencing transcription factor (REST), though direct interaction with DNA has not been implicated, we speculate that the ability of TRF2 to bind non-telomeric sequences plays a role in this (Kwon et al, 2013 ; Zhang et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unspecific binding of TRF2 to non-telomeric regions may not be surprising given that TRF2 has been shown to bind to other sequences (e.g. with G-quadruplex motifs) to functionally regulate the expression of several genes through epigenetic modification on the promoter (Imran et al, 2021 ; Mukherjee et al, 2019 ). TRF2 also plays a role in neuronal gene silencing, stem cell fate and cancer cell survival through its interaction with repressor element 1-silencing transcription factor (REST), though direct interaction with DNA has not been implicated, we speculate that the ability of TRF2 to bind non-telomeric sequences plays a role in this (Kwon et al, 2013 ; Zhang et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its specific functions at the telomeres, TRF2 performs various roles in other parts of chromatin (Baker et al, 2011 ; Imran et al, 2021 ; Mukherjee et al, 2019 ). Our study confirms that TRF2 ΔN dimers bind both telomeric and non-telomeric nucleosome arrays.…”
Section: Discussionmentioning
confidence: 99%
“…TRF2 forms t-loop structures that provide protection for telomeres from the DNA damage response and hinders the activation of ATM and NHEJ pathways, which can lead to telomere fusion and chromosomal instability [ 91 , 111 , 112 ]. By reducing its interaction with MDM2, an E3 ubiquitin ligase, Trx inhibits the ubiquitination and degradation of TRF2 [ 113 , 114 ]. Consequently, Trx may function as a positive regulator of both TRF2 and telomere maintenance, thereby exhibiting potential anti-aging effects.…”
Section: The Interplay Between Trx and Cellular Senescencementioning
confidence: 99%
“…Altogether, these findings strongly suggest that TERC-ITSs were inserted during the repair of break sites in the course of evolution through reverse transcription of TERC sequences and the telomeric repeat array. It is worth mentioning that many DNA repair proteins also interact with telomeres and that, in turn, telomere binding factors can also be recruited at internal chromosomal loci and at DNA double-strand break sites [50][51][52][53][54]. In particular, it has been shown that Ku, a key player in the non-homologous end-joining DNA repair pathway with an affinity for double-strand ends, is also able to bind to the scaRNA domain of TERC [52,55].…”
Section: Insertion Mechanisms Of Terc-itssmentioning
confidence: 99%